2021
DOI: 10.1590/acb360703
|View full text |Cite
|
Sign up to set email alerts
|

Does treatment with dutasteride or finasteride has impact on renal morphology? Experimental study

Abstract: Purpose: To investigate whether renal modifications occur following treatment with dutasteride or finasteride. Methods: Twenty-four male rats were divided into three groups: control (that received distilled water), dutasteride (0.5 mg/kg/day), and finasteride (5 mg/kg/day) groups. All administrations were given by gavage for 40 consecutive days. After inducing euthanasia, blood was collected for urea and creatinine analyses, and both the kidneys were collected for stereological analyses of kidney morphology. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We consider that in patients with renal disease, the level of plasma albumin decreases due to proteinuria, and then the colloid osmotic pressure in the blood vessels decreases, and the interstitial fluid increases, resulting in edema. In the future, the specific mechanisms of lower limb edema in patients with Eg5 deficiency can be explored through the examination of urea and creatinine in blood, and protein contents in the urine [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider that in patients with renal disease, the level of plasma albumin decreases due to proteinuria, and then the colloid osmotic pressure in the blood vessels decreases, and the interstitial fluid increases, resulting in edema. In the future, the specific mechanisms of lower limb edema in patients with Eg5 deficiency can be explored through the examination of urea and creatinine in blood, and protein contents in the urine [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…CZ1) were raised and maintained in 14 h light/10 h dark conditions at 28.5 °C. Fish lines were maintained by the standard guidelines [ 58 ]. Zebrafish embryos were obtained from the natural spawning of wild-type fish and collected at different stages according to the standard guidelines [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…50 Animal research has shown that 5ARI treatment can result in morphological and functional damage to kidneys. 68 Baig et al found Type I and Type III collagen were increased, respectively, in the interstitial cortical region and glomerulus of finasteride-treated rats, with the latter leading to glomerulosclerosis. The overall percentage of collagen in sampled kidney tissue of finasteride-treated rats was more than double that of controls.…”
Section: Ischemia-reperfusion Injury In Kidney Diseasesmentioning
confidence: 97%